Phylogenetic analysis of Dipterocarpaceae in Ketambe Research Station, Gunung Leuser National Park (Sumatra, Indonesia) based on rbcL and matK genes - ESSY HARNELLY; ZAIRIN THOMY; NIR FATHIYA (Biodiversitas Journal of Biological Diversity, 2018)
Harnelly E, Thomy Z, Fathiya N. 2018. Phylogenetic analysis of Dipterocarpaceae in Ketambe Research Station, Gunung Leuser National Park (Sumatra, Indonesia) based on rbcL and matK genes. Biodiversitas 19: 1074-1080. Gunung Leuser National Park has several Research Stations. Ketambe is one of the Research Stations which is located in Aceh Tenggara district, Aceh province. One of the timber plants family which is abundant in Leuser Mountain is Dipterocarpaceae. However, the data of species and relationship of Dipterocarpaceae in Ketambe Research Station is lack and not available. The aim of the study is to analyze the phylogenetic of Dipterocarpaceae based on rbcL and matK gene in Ketambe Research Station. This research was carried out from July 2015 to August 2016 in Ketambe Research Station and Forestry and Forest Genetics Laboratory of Molecular, Bogor Agricultural University. The method used quadrat sampling technique with purposive sampling and experimental laboratory consisting of DNA extraction, PCR, electrophoresis, and sequencing. The data analysis was done using BioEdit and MEGA6. The results showed that based on morphological identification, there were five Dipterocarpaceae species found namely; Parashorea lucida, Shorea parvifolia, Shorea lepidota, Shorea johorensis, and Hopea dryobalanoides. The phylogenetic tree based on rbcL gene showed that there were two monophyletic groups, the first group was S. johorensis, S. lepidota, and H. dryobalanoides; and the second group consisted of S. parvifolia and P. lucida. The phylogenetic tree reconstruction based on matK gene showed that Shorea parvifolia and S. johorensis were separated in two different monophyletic groups.